ANALISIS SEKTOR BASIS DI KABUPATEN BOLAANG MANGONDOW (Basic Sectors Analysis in Bolaang Mongondow Regency) - Nofri L. Wowor; Gene H. M. Kapantow; Melissa L. G. Tarore (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The purpose of this research was to analyze the sectors which were the basic sectors in Bolaang Mongondow Regency. This research was started from September to November 2019. The data used in this study were secondary data, in the form of time series data for the PDRB of Bolaang Mongondow Regency from 2013 to 2018 and the GRDP of North Sulawesi Province from 2013 to 2018. The data were obtained from official publications (website) The Central Bureau of Statistics of Bolaang Mongondow Regency and the Central Bureau of Statistics of North Sulawesi Province. The analysis method used was Location Quotient (LQ) and Dynamic Location Quotient (DLQ) analysis.Based on the results of the study, it could be concluded that the Agriculture, Forestry and Fisheries sector, the mining and quarrying sector, the real estate sector, and the education services sector were the basic sectors in Bolaang Mongondow Regency. However, for the future the Mining and Excavation sector, the Water Supply sector, Waste Management, Waste and Recycling, and the Construction sector have the potential to become the base sectors